The Spanish Language Teaching from the perspective of plural approaches: Didactic sequence for plural linguistic and cultural repertoire’s construction and expansion - Diniz, Maristela Alves de Souza; Melo Junior, Cosme da Rocha (The ESPecialist, 2024)
In this paper, we present a didactic sequence proposal directed to teaching Spanish in Elementary School, guided by the perspective of plural approaches. To the theoretical framework construction, we used bibliographical research in order to understand key concepts, such as plurilingualism and plural approaches, supported by Beacco and Byram (2007); Candelier et al (2008); Piñeiro, Guillén and Vez (2010); Melo-Pfeifer, Araújo and Sá and Santos (2011). Regarding the didactic material production, we considered the didactic sequence notion presented by Dolz and Gagnon (2010), Dolz, Noverraz and Schneuwly (2013) and Dolz (2016). The results evidenced after the material planning and production process show the document potential as a resource that favors foreign language teachers, specifically the ones in the Spanish area, allowing them to put into practice activities that present reflections on themes that guarantee a conscious and democratic education and that contribute to the development of the learner's linguistic-cultural repertoire.